LINGUISTIC BASICS OF TEACHING FOREIGN STUDENTS OF PREPARATORY DEPARTMENTS THE SCIENTIFIC SPEECH STYLE IN THE STUDY OF NATURAL DISCIPLINES - Olexandr O. Kalenyk; Tetiana L. Tsaregradskaya; Maryna Yu. Rebenko; Iryna V. Ovsiienko (Alfred Nobel University Publisher, 2022)
Improving the quality of training of foreign students at preparatory departments is a priority, which requires improving the forms, methods and technologies of teaching foreign students languages and the formation of scientific functional-linguistic style, which is the basis of communication in the professional sphere. The problem of systematic analysis of linguistic and methodological bases of teaching the scientific style of speech of foreign students at the preparatory departments has its own features and difficulties, overcoming which is associated with the search for new methodological approaches and models. The article reveals the linguistic-methodological approaches to the systematic and activity teaching of foreign students the scientific style of speech and the main components of the scientific style of speech as a kind of modern literary language using as an example teaching physics and mathematics in pre-university training. The structure of educational texts which consist of certain functional blocks and act as model for formation of communicatively-motivated kinds of speech activity is offered. The evaluation of educational and scientific texts in physics and mathematics is made in terms of their information indicators (redundancy, density of teaching material, the average index of complexity). Informational evaluation of educational texts of general and natural sciences opens the possibility of developing objective criteria for optimization and minimization of educational and professional material. The effectiveness of the proposed approach is ensured by a number of relevant and effective linguistic and methodological recommendations. The effectiveness of students' speech activity in a foreign language is determined by addressing the description of the material of the scientific language, its organization in terms of communicative and professional orientation and functional and stylistic expediency. The study of linguistic and methodological bases of teaching foreign students the scientific style of speech in the study of natural sciences allows us to conclude about the effectiveness of combining professional, linguistic and speech aspects of teaching, coordinated work of language teachers and natural sciences in forming the main components of scientific style. The method of formation of basic themes of educational texts is offered, the most important component of which is their accurate structure, sequence and logic of the statement. It is shown that the standardization of syntactic models, structures of scientific style of speech, lexical structure of scientific speech, its syntactic features are of great importance. It is shown that teaching certain types of speech activity on the material of the language of the specialty must be built differently, considering the psychological capabilities of different categories of foreign students.